Near Eastern cities from Alexander to the successors of Muhammad - Ward, Walter D. (Studies in the history of the ancient Near East, 2020)
Introduction -- Urban planning and structures in the Near East -- The tetrapolis (Antioch and Apamea) -- The decapolis (Scythopolis and Gerasa) -- Judea and Palestine (Jerusalem and Caesarea) -- The desert fringe (Petra and Palmyra) -- Conclusion.